Graphic products design & manufacture (Coquitlam, B.C., Canada : Seattle, WA, USA : Classroom Video, 2003)
A program to inspire and inform students about graphic products and design.Commercial art.
Keywords: Commercial art; Industrial design; Sound recordings -- Album covers -- Design